TINJAUAN KONSEP GREEN DESIGN PADA MEDIA TANAM LIMBAH PLASTIK TROPICAL WALL KARYA RIZAL - Dhimas Fiqry Dani Pratama; Diah Asmarandani; R. Drajatno Widi Utomo (Universitas Trisakti, 2020)
Environmental problems are not new to us. In the past, environmental problems arose due to naturalevents that occurred outside human control, for example the eruption of Mount Tambura on Sumbawa(1815) and the Krakatau Mountain in the Sunda Strait (1883). Green design is often interpreted asan environmentally sound design, or design that friendly to the environment. In other words, greendesign is a design that integrates the entire process in one unit by considering the consequences for theenvironment. One of the local young Indonesian designers, alumni from Mercu Buana University, madean innovative work that was creative and extraordinary, he made a product that greatly influenced theenvironment. The products he made were hanging pot planting media, planting media made of plasticwaste, the main ingredient was plastic plastic in which plastic can be found everywhere Rizal TropicalWall products have implemented the principles of sustainability of a product in the field of design withpay attention to environmental factors, or better known as the concept of eco-design or green design.Achieving an ecologically conscious society must begin with ‘habits’ in every action. The ‘habit’ mustbe started from and fostered so that it can develop. Starting and nurturing must be together. Remindeach other, admonish each other, and teach one another, togetherness is needed to succeed. All of theseapplications are based on when there is a feeling of caring for nature, aware of the effects that are verydangerous for us because we just ignore the environment.